(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: evaluation of the clinical characteristics, etiologies, and efficacy of phototherapy for neonatal unconjugated hyperbilirubinemia at Phu Tho Obstetrics and Pediatrics Hospital from January 2026 to April 2026. Research objects and methods: A cross-sectional descriptive study was conducted on 139 neonates diagnosed with unconjugated hyperbilirubinemia who met the criteria for phototherapy according to the NICE 2010 guidelines, from January to April 2026. Results: The study population showed a male predominance, with a male-to-female ratio of 1.72:1. Jaundice developed after 48 hours of age in 66.19% of neonates and Kramer score 4 was the most common clinical presentation. ABO incompatibility represented the leading identified pathological etiology, accounting for 14.4% of cases. Exclusive breastfeeding was associated with a significantly greater decline in serum bilirubin concentrations and a shorter phototherapy duration than formula feeding or mixed feeding (p < 0.05). Phototherapy achieved a 100% treatment success rate, and no infant required exchange transfusion. Conclusion: Phototherapy was the main treatment used in this study and showed good results in the infants who were followed up. Early screening for ABO incompatibility and maternal-fetal risk factors is recommended to optimize management.